PEMBERDAYAAN MASYARAKAT MELALUI PENINGKATAN PENGELOLAAN BADAN USAHA MILIK NAGARI (BUMNAG) DI NAGARI KAPALO KOTO KECAMATAN NAN SABARIS KABUPATEN PADANG PARIAMAN PROVINSI SUMATERA BARAT - Arya Kusuma, Doddie; Saftian Alamsyah, Dodi; Yendra, Musfi; Netrivianti, Netrivianti; Wahyudi, Wahyudi (UNES Law Review, 2023)
Nagari is a potential place for a country's economy. The amount of potential that the Nagari has can increase the income of the Nagari community, but there are still many people who are not aware of the potential they have. One of the government's efforts to overcome this problem is by empowering the community by improving the management of Nagari-Owned Enterprises (BUMNag). This study uses a qualitative approach. Data obtained while in the field were recorded in field notes. After all the data has been collected, the next step is to analyze all the data, both primary and secondary data obtained by the researcher from the beginning to the end of the study. The results of this study indicate that community empowerment through improving the management of Nagari-Owned Enterprises is going well through the stages of increasing knowledge and skills, training, mentoring, and evaluation, and having several business units within it such as sharia savings and loans, waste banks, and agriculture. In this study, BUMNag management and the community were actively involved in every business program and with this community involvement community empowerment through BUMNag could utilize the natural potential and the potential of the community in the area.